1999
DOI: 10.1002/pc.10392
|View full text |Cite
|
Sign up to set email alerts
|

Use of acoustic emission to characterize corrosion fatigue damage accumulation in glass fiber reinforced polyester laminates

Abstract: The acoustic emission technique has been used to characterize fatigue damage accumulation in glass fiber woven roving (O/90°) polyester laminates after prolonged exposure in sea water. Comparisons were made with fatigue tests of "as-received" laminate under similar loading conditions. Pre-exposure has been found to substantially reduce the fatigue strength of the composite. Acoustic emission monitoring during fatigue testing has shown that the amplitude distribution of the acoustic events shifts from predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 9 publications
1
31
0
Order By: Relevance
“…Attribution of each cluster to one particular damage mechanism was done by using previous results for clustering based on the amplitude only. Several authors [16,17,18,19] have shown that acoustic events with lower amplitudes are associated to matrix cracking whereas those with higher amplitudes are associated to fibre breakage. The intermediate range corresponds to interface damages.…”
Section: Acoustic Emission (Ae)mentioning
confidence: 99%
“…Attribution of each cluster to one particular damage mechanism was done by using previous results for clustering based on the amplitude only. Several authors [16,17,18,19] have shown that acoustic events with lower amplitudes are associated to matrix cracking whereas those with higher amplitudes are associated to fibre breakage. The intermediate range corresponds to interface damages.…”
Section: Acoustic Emission (Ae)mentioning
confidence: 99%
“…[14] Kotsikos and al. [15][16] and Benzeggagh and al. [17][18], all these authors and many others have classified the amplitudes into three or four groups, as appropriate, to involve the various failure modes of composite materials.…”
Section: Fig3 Stress-strain Responses Under Tension Loading Gfrpmentioning
confidence: 99%
“…Forty years of research have led to the agreement that there are four main damage mechanisms identifiable in composite materials by their acoustic emission Bsignature^ [36,37]: (i) matrix cracking, (ii) interfacial debonding, (iii) fibrematrix friction/fibre pull-out, and (iv) fibre breakage. Researchers have used many different methods to distinguish these damage mechanisms during mechanical testing including, but not limited to, classification of acoustic signature [20,[37][38][39], amplitude and frequency distribution analysis [20,, and analysis of different features of the waveform [37,44]. Figure 3 shows a typical AE signal and the parameters that are commonly used for analysis of AE-generating damage events.…”
Section: Acoustic Emission Monitoringmentioning
confidence: 99%